Hedonic capacity in a Chinese community population sample: psychometric properties of the dimensional anhedonia rating scale (DARS) and exploration of gender differences - Qi Wang; Yankun Wu; Yunshu Zhang; Keqing Li; Yun-Ai Su; Tianmei Si (BMC Psychology)
Abstract Background A reduction in the hedonic capacity, that is, anhedonia, is closely associated with the onset of depression, which negatively affects mental health and life satisfaction. However, simple and comprehensive tools to assess hedonic capacity in community-dwelling adults are lacking. Methods An online survey was conducted from March to April 2023, recruiting 678 community-dwelling adults. We assessed the psychometric properties of the Chinese version of the Dimensional Anhedonia Rating Scale (DARS) and used multivariate linear regression to examine gender differences in hedonic capacity and its contributing factors. Results The Chinese version of the DARS demonstrated excellent reliability and validity in the non-clinical sample. Higher education levels and being female were associated with better hedonic capacity, while sleep disturbances and living alone were linked to lower hedonic capacity. Additionally, gender differences were found in the factors affecting hedonic capacity: for males, living alone and sleep disturbances had a negative impact, whereas for females, higher education levels were positively associated with hedonic capacity. Limitations There was a lack of structured diagnoses among community samples. Conclusion The Chinese version of the DARS is an effective tool for assessing hedonic capacity, i.e. screening for depression in community-dwelling populations. The observed gender differences in hedonic capacity imply that future mental health services could be more effective if adapted based on gender.